½W - 3 and ½W + 3
(½W - 3) + (½W + 3) = ½W + ½W - 3 + 3 = W
|(½W - 3) - (½W + 3)| = |½W - 3 - ½W - 3| = |½W - ½W - 3 - 3| = |-6| = 6
(The difference between two numbers can be calculated by subtracting one from the other and ignoring the sign; |n| is the value of n ignoring the sign.)
It is 14 and 6.
17 and 6
11 and 6
6 and 3
the answer is 6 and 4
3 and 9 Difference: 9-3=6 Sum: 9+3=12
6 and 6
11 and 5
The two numbers are 10 and 4
6 and 8
It is 14 and 6.
8 and 6 have a difference of 2 and a sum of 14.
6 and -4
29 & 35
The numbers are 53 and 47
The numbers are 18 and 12
10 and 6